Complex Regional Pain Syndrome Following Distal Radius Fracture: Does Surgical Method Matter? - Ludvigsen, Trine; Hammer, Ola-Lars; Fevang, Jonas Meling; Matre, Kjell; Dybvig, Eva Hansen; Randsborg, Per-Henrik (Journal of Wrist Surgery, 2024)
The purpose of this study was to compare the risk of complex regional pain syndrome (CRPS) following surgical treatment of distal radius fractures (DRFs) with either a volar locking plate (VLP) or an external fixator (EF).Data from two randomized controlled trials (RCTs) were merged and analyzed. A logistic regression analysis was conducted to identify independent risk factors for the occurrence of CRPS.A total of 322 patients were included from the two RCTs; 159 patients were operated upon with VLP and 163 patients with EF. CRPS was diagnosed in 6 patients treated with VLP (4%) and in 16 patients receiving EF (11%), overall 22 cases of CRPS (7%). None of the other independent risk factors had a significant influence on the risk for CRPS (all p > 0.05).Patients treated with an EF had a higher risk of developing CRPS compared to those treated with a VLP. We found no other independent variable predicting CRPS.III.
Keywords: complex regional pain syndrome; distal radius fracture; external fixator; volar locking plate; Budapest criteria